Parametric study of sputtering microchannels on silicon using a focused ion beam - Siti Fatimah binti Mohd Shahar (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Focused ion beam (FIB) has been widely used in microelectronic applications as it has the capabilities to perform both imaging and sputtering down to the nanometer scale. Essential FIB parameters include the accelerating voltage, beam current, beam diameter, pixel spacing, dwell time and scanning time, spot size, and beam overlap. The set of input parameters used are accelerating voltage, beam current, beam diameter, scanning time, and dwell time. The output results were depth, gap between the channels, channels width, and surface roughness. In this research, the main experimental work had been divided into two phases. Phase one aim is to identify the suitable set of parameters that can pursue the targeted geometry. Scanning time and dwell time are set to be fixed with the value of 3.0mins and 1.0µs respectively. Whereas the second phase is done by using Central Composite Design (CCD) method from Response Surface Methodology (RSM) to determine the optimum set of parameter that could achieve the targeted geometry and surface finish. During this phase, the scanning time and dwell time are varied to investigate the relationship between them to the targeted geometry. The target material was silicon <100> with 250 µm thickness. The work found that the best set of FIB parameter that can provide an optimum response is when the accelerating voltage used is 16keV, beam current 4.0pA, beam diameter 13.0nm, while the dwell time and scanning time are 1.00µs and 3.00mins respectively. The gap between the channels and the channels width generated are 237.178nm and 363.904nm respectively while the surface roughness obtained is 0.1551nm. During the second phase, the relationship between dwell time and scanning time appear to be weak. These parameters do not highly influence compared to accelerating voltage, beam current, and beam diameter (first phase), where the dimensional accuracy have three essential categories which are no data result, poor dimensional accuracy (large difference up to 66.56nm), and good dimensional accuracy (small difference and reaching 0.0nm). The effect on different input parameters used also can be observed such as shallow depression of the microchannels, lower walls in between the channels, wall swelling, and re-deposition of the ions.